2015
DOI: 10.1590/0004-282x20140194
|View full text |Cite
|
Sign up to set email alerts
|

Is functional dependence of Duchenne muscular dystrophy patients determinant of the quality of life and burden of their caregivers?

Abstract: Objective:The relationship between functional dependence and quality of life (QOL) in Duchenne muscular dystrophy (DMD) patients and burden and QOL in caregivers is not clear. This study investigated possible relationships between functional dependence/QOL of DMD patients and QOL/burden of caregivers. Method: This study included 35 boys (6-17 years) and respective caregivers (above 21 years). Caregivers answered to World Health Organization Quality of Life and Zarit Burden Interview questionnaires. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 29 publications
2
37
1
5
Order By: Relevance
“…One French study (Martigne [28]) reported a mean age of ambulation loss of 10 years. Unsurprisingly similar results were found in six studies reporting wheelchair use, four as percentage [2932] and two as time to first use [19, 33]. Percentage use and time to use were unsurprisingly similar to those for loss of ambulation.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…One French study (Martigne [28]) reported a mean age of ambulation loss of 10 years. Unsurprisingly similar results were found in six studies reporting wheelchair use, four as percentage [2932] and two as time to first use [19, 33]. Percentage use and time to use were unsurprisingly similar to those for loss of ambulation.…”
Section: Resultssupporting
confidence: 74%
“…The percentage of all DMD patients on assisted ventilation varied very widely from 0% in a Brazilian study of boys (mean age 11 years) by de Moura [29],0.7% in a multinational European study (mean age 13 years) by Vry [40] and 22% in a Japanese study (mean age not reported but most individuals described as less than 20 years old) (Nakamura [26]). Variation by disease progression was shown in the US study by Mayer [27] with a gradual decline from 126.6% predicted forced vital capacity (FVC) in the under 6 years age group to 7.3% predicted FVC in those aged 20 to 22 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is usual that the mother takes on the job of the main caregiver of patients with DMD. Studies conducted in Brazil demonstrated that the mother is the main caregiver of children with DMD [18,19]. Data from our group confirm these findings.…”
Section: The Caregiver In Duchenne Muscular Dystrophysupporting
confidence: 88%
“…In total, seven articles measured overall caregiver burden, [9][10][11][12][13][14]22 five HRQoL, [10][11][12][13][14] four stress, 14,[16][17][18] six work life, informal care, and/or associated cost burden, 11,[19][20][21][22]28 five family problems and functioning, 9,14,15,23,24 six sleep, 13,15,21,[25][26][27] five pain and/or discomfort, 12,13,21,23,24 two strain, 13,28 nine anxiety and/or depression, [12][13][14][15]23,24,[26][27][28] two overall caregiver health, 23,24 one self-esteem and mastery (i.e. that life chances are under one's own control), <...>…”
Section: Resultsmentioning
confidence: 99%